2017
DOI: 10.1080/08037051.2017.1344539
|View full text |Cite
|
Sign up to set email alerts
|

Association between cotinine-verified smoking status and hypertension in 167,868 Korean adults

Abstract: This large observational study showed that cotinine-verified current smoking and unobserved smoking were inversely associated with hypertension in Korean adults, especially only in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…5-7 Recently, we reported that cotinine-verified smoking was negatively associated with HTN independent of covariates, especially in men. 8 However, the cross-sectional design of the previous studies prevented clarification of a causal relationship between chronic smoking and HTN.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5-7 Recently, we reported that cotinine-verified smoking was negatively associated with HTN independent of covariates, especially in men. 8 However, the cross-sectional design of the previous studies prevented clarification of a causal relationship between chronic smoking and HTN.…”
Section: Resultsmentioning
confidence: 99%
“…8 As described previously, unobserved smoking includes secondhand smoke (SHS), environmental tobacco smoke exposure, and under-reporting of exposure to cigarette smoke. 8 Previous studies have shown discordant results for the association between SHS and HTN. 8,25-27 However, those studies included different populations and were mostly cross-sectional in design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, they concluded that this urinary cotinine level was reasonable because their crosssectional study showed that the degree of agreement between self-reported and cotinine-verified smoking status was almost perfect. 19 Exposure to environmental tobacco smoke can affect the urinary cotinine level. Kim et al 13 defined unobserved smokers as cotinine-verified current smokers among the self-reported never smokers.…”
Section: Disclosuresmentioning
confidence: 99%